Disallowance analysis through the audit of accounts performed by nurses: an integrative review - Cinthia Prates Vigna; Paula Buck de Oliveira Ruiz; Antônio Fernandes Costa Lima (Revista Brasileira de Enfermagem, 2020)
ABSTRACT Objective: Evidence the scientific production on the analysis of disallowances through the audit of accounts made by nurses. Method: Integrative literature review whose sample of ten articles was selected on the basis of The Cumulative Index to Nursing and Allied Health Literature, Latin American and Caribbean Literature in Health Sciences, EMBASE, Scielo, Web of science, Virtual Health Library and on the portal PubMed. Results: The ten articles obtained were published in Brazil, 80% covering hospital contexts; with a quantitative (50%), exploratory (40%) and descriptive (60%) approach. Studies investigating the occurrence of disallowance prevailed to identify the most impacting items on billing and possibilities for improvements in the process of auditing accounts by nurses. Conclusion: The verticalized knowledge of the disallowance analysis process is essential to identify non-conformities and propose improvements, aiming at assistance quality, adequate billing and consequent financial sustainability to health organizations.